Inelastic resonant tunnelling through adjacent localised electronic states in van der Waals heterostructures - E. E. Vdovin; K. Kapralov; Yu. N. Khanin; A. Margaryan; K. Watanabe; T. Taniguchi; C. Yang; S. V. Morozov; D. A. Svintsov; K. S. Novoselov; D. A. Ghazaryan (npj 2D Materials and Applications)
Abstract Van der Waals heterostructures offer unprecedented opportunities to design next stage functional electronic 2D devices. Most architectures of those devices incorporate large bandgap insulator – hBN as an encapsulating or tunnel barrier layers. Here, we use an architecture of gated vertical tunnelling transistors to study a generic phenomenon of electron resonant tunnelling through adjacent localised electronic states in hBN barriers. We demonstrate that in the case of two localised electronic states, the tunnelling can be of inelastic nature giving rise to explicitly strong resonant features. It allows accurate tunnelling spectroscopy of delicate features of emitting and collecting layer electronic density of states, such as second neutrality point bandgap of moiré monolayer and electric field induced bandgap of Bernal bilayer graphene. Our findings enrich the perception of interaction mechanisms among the localised electronic states in hBN barriers paving the way for future explorations into their applications.